Menganalisis Identitas-Identitas Yesus Kristus dalam Buku Apologia Pertama Yustinus Martir - Adrianus Musu Sili (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2026)
This research discusses the identity of Jesus Christ in the book Apology I written by Justin Martyr. The researcher uses historical literature analysis to deeply examine Yustinus Martir's thoughts on the identity of Christ in his book. The results of the study found that the identity of Christ in the book Apology I highlights the historical analogy and divinity of Jesus as the Son of God to state that Jesus existed before all times. The Jewish prophets had also prophesied about Him in the Old Testament so that Jesus came to fulfill the hope of Israel. Moreover, Justin also compared  Jesus’ identity as the Son of God with that of Jupiter’s . These identities  were able to influence the views of Christian Christology in the second century AD.AbstrakPenelitian ini membahas identitas Yesus Kristus dalam buku Apologi I yang ditulis oleh Yustinus Martir. Penelitian  menggunakan analisis literatur historis untuk mengkaji lebih dalam pemikiran Yustinus Martir tentang identitas Kristus dalam bukunya. Hasil penelitian menemukan bahwa identitas Kristus dalam buku Apologi I menonjolkan analogi historis dan keilahian Yesus sebagai Anak Allah untuk menyatakan bahwa Yesus telah ada sebelum segala zaman, Para nabi Yahudi juga telah menubuatkan-Nya dalam Perjanjian Lama sehingga Yesus datang untuk menggenapi harapan Israel, dan perbandingan antara Yesus sebagai Anak Allah dengan Putra Jupiter. Idenitas-identitas Yesus Kristus tersebut mampu mempengaruhi pandangan Kristologi Kristen pada abad kedua Masehi.